Radiative pumping and propagation of plexcitons in diffractive plasmonic crystals - Zakharko, Yuriy; Rother, Marcel; Graf, Arko; Hähnlein, Bernd; Brohmann, Maximilian; Pezoldt, Jörg; Zaumseil, Jana (Nano letters, 2018)
Strong coupling between plasmons and excitons leads to the formation of plexcitons: quasiparticles that combine nanoscale energy confinement and pronounced optical nonlinearities. In addition to these localized modes, the enhanced control over the dispersion relation of propagating plexcitons may enable coherent and collective coupling of distant emitters. Here, we experimentally demonstrate strong coupling between carbon nanotube excitons and spatially extended plasmonic modes formed via diffractive coupling of periodically arranged gold nanoparticles (nanodisks, nanorods). Depending on the light-matter composition, the rather long-lived plexcitons (>100 fs) undergo highly directional propagation over 20 μm. Near-field energy distributions calculated with the finite-difference time-domain method fully corroborate our experimental results. The previously demonstrated compatibility of this plexcitonic system with electrical excitation opens the path to the realization of a variety of ultrafast active plasmonic devices, cavity-assisted energy transport and low-power optoelectronic components.
Gesehen am 11.03.2020